2019
DOI: 10.1039/c9nr03402a
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic nanobubbles for targeted gene delivery by focused ultrasound

Abstract: Cationic biosynthetic nanobubbles combined with ultrasound lead to significantly improved gene transfection efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Moreover, the cavitation effect of ultrasound increased the permeability of the cell membrane and facilitated the entry of the drug into cells, greatly improving the therapeutic effect of the drugs. [28][29][30][31] The experimental results confirmed that G250-TNBs combined with UTND more significantly inhibited the proliferation of tumor cells and promoted their apoptosis than G250-TNBs alone, and showed a superior effect compared with TEM alone (P<0.05). This phenomenon is consistent with previous studies, 15 that is, UTND can cause the concentrated release of drugs in NBs, thereby improving the anti-proliferative effect of drugs while reducing the influence of drugs on the surrounding normal cells and reducing their side effects.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, the cavitation effect of ultrasound increased the permeability of the cell membrane and facilitated the entry of the drug into cells, greatly improving the therapeutic effect of the drugs. [28][29][30][31] The experimental results confirmed that G250-TNBs combined with UTND more significantly inhibited the proliferation of tumor cells and promoted their apoptosis than G250-TNBs alone, and showed a superior effect compared with TEM alone (P<0.05). This phenomenon is consistent with previous studies, 15 that is, UTND can cause the concentrated release of drugs in NBs, thereby improving the anti-proliferative effect of drugs while reducing the influence of drugs on the surrounding normal cells and reducing their side effects.…”
Section: Discussionmentioning
confidence: 61%
“… 99 , 102 Because of their inherent advantageous physicochemical features and their facile production methods, as well as their ability to disrupt the blood–brain barrier (BBB) discovered in recent years, 103 NBs have received widespread attention especially in the biomedical field. 18 Their biomedical applications include nanomotor-based machinery, 104 drug delivery, 23 , 105 gene delivery, 106 cancer immunotherapy and chemotherapy, 107 , 108 and wound-healing and tissue regeneration. 19 …”
Section: Nbs: Formation and Stabilitymentioning
confidence: 99%
“…Due to their very small size, they are able to traverse intercellular gaps and deposit deep into tissues, perhaps making them less desirable to endothelial transfection. They are desirable for applications such as tumor targeting, where they are able to infiltrate deep into the tumor for treatment [168]. They were also shown to be safer to cells than microbubbles, causing transfection in an in vitro model without impacting cell viability [169].…”
Section: Optimizing Bubble Size and Charge For Deliverymentioning
confidence: 99%